Dimethylaminoethyl methacrylate copolymer-siRNA nanoparticles for silencing a therapeutically relevant gene in macrophages1. Issue 4 (10th April 2015) - Jain, Ratnesh; Dandekar, Prajakta; Loretz, Brigitta; Koch, Marcus; Lehr, Claus-Michael
<x xml:space="preserve">Abstract</x> DMC nanoparticles target Bfl1/A1 gene in lung macrophages and effective silencing of Bfl1/A1 gene by DMC nanoparticles paves the way for research on alternative treatment strategies for tuberculosis.